Pengolahan bioarang sebagai pengganti biogas untuk mendukung proses roasting pengolahan kopi arabica dan ketahanan energi - Benedictus Mardwianta; abdul haris subarjo; Dedet Hermawan Setiabudi; Munawar Husaini (Institut Teknologi Dirgantara Adisutjipto, 2021)
Processing of waste biochar into briquettes as a substitute for biogas to support the roasting process of Arabica coffee processing is an alternative energy innovation as a substitute for conventional charcoal derived from wood and biogas from LPG as well as to support energy security. Briquette is a material that is strongly influenced by the nature and type of the materials that make it up. This study aims to determine the effect of the composition of briquettes with a mixture of coffee husk waste and sawdust on the calorific value, moisture content, ash content, and density test. The method used is experimental. In composition III the density value is the highest because the amount of sawdust is the most. because with the treatment of the compressive force manually, the charcoal particles will experience compression in accordance with the given compressive force. The results of the research on composition I yielded a calorific value of 6052 cal/gr, composition II yielded a calorific value of 6122 cal/gr and composition III yielded a calorific value of 6333 cal/gr. The results of the ash content test of SNI 01-6235-2000 regarding charcoal briquettes, the permissible ash content does not exceed the value of 8%. The ash content produced in composition III is according to the specified standard